ETIKA BISNIS ISLAM MENURUT IMAM AL-GHAZALI DAN YUSUF AL-QARADHAWI - Fitriani; Sri Deti; Sri Sunantri (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2022)
Islamic business ethics is a moral reference as part of the form of Akhlaqul Karimah in sharia-based business. Islamic business norms and ethics are based on good faith and mutual pleasure ('an taradhin) between parties while still adhering to the halal and toyib aspects. In carrying out business activities, al-Ghazali and Yusuf Qardhawi emphasize to always be guided by Islamic business ethics. The formulation of the problem in this thesis research is how al-Ghazali thinks about Islamic business ethics, how al-Ghazali thinks about Islamic business ethics and how is the comparison (similarity/difference) between al-Ghazali's thoughts and Yusuf Qardhawi's. In the preparation of this thesis the author uses data collection techniques in the form of library research, as the approach is used a comparative approach. Researchers used qualitative data analysis, namely data that cannot be measured or assessed with numbers directly. The result of the discussion that according to al-Ghazali and Yusuf Qardahwi, ethics (morality) is the mental state that is the source of the birth of an act in which the act was born spontaneously, easily, without calculating the benefits. In carrying out business activities, al-Ghazali and Yusuf Qardhawi emphasized to always be guided by Islamic business ethics, al-Ghazali broadly classifies them into 8 ethics, namely: 1) Business activities must be based on elements of fairness, goodness, virtue and the absence of displeacure 2) There must be clarity between businesses 3) Fostering good business relationships and trusts 4) Receivables payables must be settled immediately before the agreed time 5) Reduce margins by selling cheaper, and in turn increase profits 6) Business activities not only to pursue world profits alone , 7) Keep away from syubhat transactions, and 8) Gain profit with existing risk considerations. While Yusuf Qardhawi classified it into 4 Ethics, namely: 1) Ethics in the field of Production, 2) Ethics in the field of Consumption, 3) Ethics in the field of Circulation, and 4) Ethics in the field of Distribution. The actualization of al-Ghazali's thinking on business ethics and its role in the National economy is that the main principle in the formulation of Islamic economics is towards maslahah. Meanwhile, Yusuf Qardhawi sees that contemporary businesses contribute greatly in answering ethical issues in doing business comprehensively. In his thinking reflected that the business ethics that he initiated is a form of business professionalism that will always maintain business continuity.